Correlación entre la precipitación pluvial y la densidad y composición del zooplancton de ocho represas del estado de Aguascalientes, México - Hernández-Rodríguez, Miguel Ángel; Santos-Medrano, Gustavo Emilio; Quintero-Díaz, Gustavo; Rico-Martínez, Roberto (Revista de Biología Tropical, 1999)
Potential effects of rainfall on the density and composition of the zooplankton of eight reservoirs of Aguascalientes was studied. To study the effect of differences in rainfall, a zooplankton sample in each reservoir in August 16th and 17th, 1997 and March 27th, 1998 was taken. These two months correspond to the wettest and the driest of the year in Aguascalientes, respectively. Alkalinity, BOD, chlorides, chlorophyll, COD, conductivity, dissolved oxygen, orthofosfates, pH, phosphates, sulfates, temperature, and total dissolved solids, were also analysed for each reservoir to understand the effect of nutrient loading in zooplankton densities. In all cases, nutrient loads of orthophosphates· were higher during the driest month. During the analysis of the zooplankton density data and composition, an interesting relationship between the composition of the zooplankton (larger than 53μ) and the precipitation was found. A positive correlation between small zooplankton (Protozoa and Rotifera) and the wettest month, and a negative correlation between large zooplankton (Cladocera and Copepoda) and the driest month were also found. Also, orthophosphates were negatiyely eorrelated with total density of zooplankton during the wettest month. The meaning of these correlations in the context of their biological and statistical significance is discussed.